"For he had told them"– Mordecai the Jew and Jonah the Hebrew. Issue 2 (2nd July 2020) - Seidler, Ayelet
ABSTRACT: In Esth 3, 2-4 and Jonah 1, 6-12 we find fateful confrontations between the main character (Mordecai and Jonah, respectively) and a group of bystanders (the servants of the king; the passengers on the ship). In both instances, information that the hero conveys during his exchange with the bystanders is revealed in retrospect by the narrator, using an expression unique to these two narratives: "for he had told them…." In this article I propose that each narrative contrasts the hero's self-identity with the manner in which his identity is understood by his interlocutors. The rhetorical technique of retrospection serves the narrator in emphasizing the conflict. The centrality of the question of identity in each exchange, and the use of the same rhetorical device and identical words in each case, lend support to the possibility of reading these as analogous narratives. The article concludes with a discussion of the significance of this analogy.